Data on the pupae and behavior of the adults of Dirphia araucariae - Borges, Jácomo Divino; Carneiro, Maurízia de Fátima; Almeida, Armando Antunes de (Pesquisa Agropecuaria Brasileira, 2014)
The pupae length, diameter and volume, for males and females from two particular places and the influence of temperature at 20°C and 25°C on the behavior of the adults of Dirphia araucariae Jones, 1908 (Lepidoptera: Attacidae) was studied. The pupae length was 3.29 cm and 3.65 cm, and 3.05cm and 3.54 cm; the diameter was 1.35cm and 1.51 cm and 1.19cm and 1.39 cm, and the volume was 3.17 cm3 and 4.52 cm and 2.42 cm3 and 3.65cm3 respectively from Capão Bonito, SP and Congonhinhas, PR, Brazil. The stages of pre-oviposition, oviposition and post-oviposition lasted on average 2.00, 5.58 and 2.75 days, respectively, at 20°C, and 1.75, 5.08 and 2.25 days at 25°C. The mean number of eggs per female was 243.50 and 239.17 eggs, and the percentage of fertile eggs was 61.02% and 47.15%, at 20°C and 25°C, respectively.